Numerical Analysis of Zipper Fracturing Using a Non-Planar 3D Fracture Model - Wang, Zhen; Yang, Lifeng; Gao, Rui; Xu, Guanshui; Liu, Zhe; Mo, Shaoyuan; Fan, Meng; Wang, Xin (Frontiers in Earth Science, 2022)
Zipper fracturing has become one of the routine reservoir stimulation methods for developing unconventional resources such as shale oil and gas. A non-planar 3D fracture propagation model is used to study the fracture propagation behavior of zipper fracturing. The effects of stage time lag, staggered perforation cluster spacing, and horizontal principal stress contrast on the fracture geometry are analyzed through numerical simulation. The simulation results show that increasing the stage time lag can increase the fracture length and improve inter-well stimulation. For the formation with higher horizontal principal stress contrast, the staggered perforation cluster spacing has a minimum effect on the fracture configuration of zipper fracturing. For the formation with lower horizontal principal stress contrast, the fractures follow the curved paths and intersect with each other, which potentially has adverse effects on the stimulation of the subsequent stages.